(untitled) (Annals of Medical Research, 2021)
Aim: With the increase in the geriatric population, admissions to emergency units are increasing each day. This study aims to determine the perspective and attitudes of emergency specialists towards geriatric patients, and to form a training program for emergency medicine to improve the quality of patient care. Materials and Methods: We conducted a complementary study designed as a survey. At the end of the study period, the data collected were recorded in SPSS for Windows 15.0 (SPSS Inc.®, Chicago, ABD) program package and statistically analyzed. The Chi-square, Yates corrected chi-square and the Fisher’s exact tests were used in order to define the relationship between the parameters. The level of significance was accepted as p0.05.Results: 335 physicians working in the emergency units responded to the survey questionnaire and participated in the study. Overall, 74.7% of the participants worked in the institutes where a geriatric division or department was not present. No specific division of geriatrics was present in the institute where 60.5% of the participants worked. 79.4% of the participants mentioned that hospitalization of geriatric patients was avoided compared with that of younger patients where they worked. Furthermore, 37.3% of research assistants and 13.1% of the specialists mentioned that they had no training in geriatrics. 68.2% of the participants stated that they felt sufficient in approaching geriatric patients and 67% stated that they felt sufficient in communication with them. The participants desired training mostly in drug interactions, elder abuse and communication. 226 (68.9%) the emergency unit doctors stated that they had patients who had been subjected to elder abuse. Finally, 72.8% of the pariticipants felt no unwillingness in case of a need for resuscitation to elderly patients with no oncological disease or those who were not accepted to be in their terminal period.Conclusion: Training of emergency unit specialists for the management of geriatric patients is insufficient and needs to be revised.